Obtaining green energy from dry-thermophilic anaerobic co-digestion of municipal solid waste and biodiesel waste. (June 2018) - Zahedi, S.; Sales, D.; García-Morales, J.L.; Solera, R.
Abstract : This study has been conducted to optimise the dry-thermophilic anaerobic co-digestion of two different types of real waste (municipal solid waste and biodiesel waste) in a semi-continuous feeding regime, under high organic loading rates (OLRs) or low hydraulic retention times (HRTs). For this purpose, different high OLRs (from 10 to 34 g [VS] l −1  d −1 ) or low HRTs (from 10 to 4.4 d) were investigated in a continuously stirred tank reactor. Optimal conditions (257 ml [CH4 ] g −1 VS; 6.03 ± 0.43 l [CH4 ] l −1  d −1 ; 16.3 ± 2.3 × 10 −12  l [CH4 ] cell −1  d −1 ) were obtained at 4.4 d HRT (OLR = 23 g [VS] l −1  d −1 ), in which the average values of the ratios of Eubacteria:Archaea and hydrolytic-acidogenic bacteria:acetogens were 95:5 and 87:8, respectively. Highlights: Co-digestion of municipal solid waste and biodiesel waste has been studied. Brief supplementation with BW (0.5%) greatly enhances the bioenergy of MSW. High organic loading rates or low hydraulic retention times were employed. The microbiota involved in the process of AD were also studied. Optimal conditions of anaerobic co-digestion were obtaining at 4.4 d.